2019
DOI: 10.1002/chem.201804723
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Pre‐organized N‐Donor Group on the Coordination of Trivalent Actinides and Lanthanides by an Aminopolycarboxylate Complexant

Abstract: The thermodynamic influence of a pre‐organized N‐donor group on the coordination of trivalent actinides and lanthanides by an aqueous aminopolycarboxylate complexant has been investigated. The synthesized reagent, N‐2‐methylpicolinate‐ethylenediamine‐N,N′,N′‐triacetic acid (EDTA‐Mpic), resembles ethylenediamine‐N,N,N′,N′‐tetraacetic acid (EDTA) with a single acetate pendant arm replaced by a 6‐carboxypyridin‐2‐ylmethyl group. The rigid N‐donor picolinate functionality has a profound impact on ligand protonatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…The combination of applied extraction properties of phenanthroline diphosphonates as well as the synthetic availability of pyridine ligands determined the choice of the series of phosphorous containing ligands for this study (Table 1). It is also worth noting that from the fundamental point of view the complexation features and coordination chemistry of polydentate N,O-donor ligands are prominently described only for 5f-and 4f-elements, [29][30][31][32][33][34] whereas their binding with d-elements is poorly described.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of applied extraction properties of phenanthroline diphosphonates as well as the synthetic availability of pyridine ligands determined the choice of the series of phosphorous containing ligands for this study (Table 1). It is also worth noting that from the fundamental point of view the complexation features and coordination chemistry of polydentate N,O-donor ligands are prominently described only for 5f-and 4f-elements, [29][30][31][32][33][34] whereas their binding with d-elements is poorly described.…”
Section: Introductionmentioning
confidence: 99%
“…Although HDEHP mixed with TODGA or T2EHDGA has also been studied, corresponding separations are not as efficient as those using HEH­[EHP]. , All these studies focusing on HEH­[EHP] in combination with HEDTA have shown results that surpassed the conventional TALSPEAK process; however, a relatively high pH range is still needed (between 3 and 4), which requires a pH buffer and poses implementation challenges in industrial settings, where the upstream acidity is very high (on the order of molars of HNO 3 ) and downstream salts are undesirable. More recently, several structural modifications of acetic acid derivatives have been made to explore their applicability to more acidic conditions; resulting separation factors decreased considerably from 50–80 at pH 3–4 to <30 at pH < 2. However, in the past 50 years, nearly all efforts have concentrated on only one class of hold-back reagents, the polyaminocarboxylates, especially DTPA, ,,, HEDTA, , TTHA, or DPA (dipicolinic acid)…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophilic N-donor complexing agents are used in several solvent extraction processes developed to separate actinides from lanthanides. Such separations may play a role in future advanced nuclear fuel cycles. On the basis of the chemistry of the TALSPEAK process, , actinide and lanthanide ions are co-extracted, followed by selective stripping of actinides using N-donor complexing agents such as aminopolycarboxylates or sulfonated N-heterocyclic compounds. …”
Section: Introductionmentioning
confidence: 99%